2008
DOI: 10.4049/jimmunol.180.1.630
|View full text |Cite
|
Sign up to set email alerts
|

Selective Estrogen Receptor-β Agonists Repress Transcription of Proinflammatory Genes

Abstract: In addition to their role in the development and function of the reproductive system, estrogens have significant anti-inflammatory properties. Although both estrogen receptors (ERs) can mediate anti-inflammatory actions, ERβ is a more desirable therapeutic target because ERα mediates the proliferative effects of estrogens on the mammary gland and uterus. In fact, selective ERβ agonists have beneficial effects in preclinical models involving inflammation without causing growth-promoting effects on the uterus or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 62 publications
2
59
1
3
Order By: Relevance
“…Es- tradiol exerts activity through two distinct estrogen receptors (estrogen receptor ␣ [ER␣] and ER␤) that populate different tissues and cell lines (56). Estrogen receptor ␤ has previously been shown to have anti-inflammatory activity with repression of multiple cytokines in immune cells, whereas ER␣ is more associated with anabolic activity in the female mammary gland and reproductive tract (57). Which receptor and which pathway are more important for producing asymptomatic S. pyogenes carriage are unknown, but the murine vaginal carriage model could provide valuable insight into estradiol and its link to carriage and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Es- tradiol exerts activity through two distinct estrogen receptors (estrogen receptor ␣ [ER␣] and ER␤) that populate different tissues and cell lines (56). Estrogen receptor ␤ has previously been shown to have anti-inflammatory activity with repression of multiple cytokines in immune cells, whereas ER␣ is more associated with anabolic activity in the female mammary gland and reproductive tract (57). Which receptor and which pathway are more important for producing asymptomatic S. pyogenes carriage are unknown, but the murine vaginal carriage model could provide valuable insight into estradiol and its link to carriage and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter ERb1 protein may be more stable than the long form as it is potentially missing the binding site for the ubiquitin ligase, carboxyl terminus of HSC70-interacting protein (CHIP), required for inducing ERb1 proteasomal degradation (Tateishi et al 2006). Functional differences between the long and short forms of ERb1 have been described, in particular associated with anti-inflammatory activities of ERb1 (Bhat et al 1998, Tateishi et al 2006, Cvoro et al 2008, Saijo et al 2011. Furthermore, it has been shown that Pescadillo ribosomal biogenesis factor 1 (PES1) differentially affects ERb1 and ERa at a posttranslational level and may, in part, be responsible for the altered ratios of ERa/ERb seen consistently during breast tumorigenesis (Cheng et al 2012, Thomas & Gustafsson 2012.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Les estrogènes jouent un rôle complexe dans l'inflammation in vitro et in vivo (Straub, 2007, pour revue ;Cvoro et al, 2008).…”
Section: Les Récepteurs Nucléaires Aux Estrogènes : Reα Et Reβunclassified